Nominal and real effective krone rate indices for Denmark 1875-2002 - Kim Abildgren (Danmarks Nationalbank, 2004)
This paper constructs annual trade-weighted nominal and real effective exchange rate indices for Denmark covering the period since the introduction of the krone as the Danish currency unit in 1875. Two real effective krone rate indices with respectively wholesale prices and consumer prices used as deflators are calculated. All indices are constructed as geometrically weighted chain indices with current trade weights based on Denmark's foreign trade in goods with 15 of its largest trading partners. During each year in the period since 1875 these 15 countries accounted for at least 78 per cent of Denmark's total foreign trade in goods.
Keywords: F31; N23; N24; 330; Danish krone exchange rates; Effective exchange rates; History of exchange rates; Preisindex; Wechselkurs; Kaufkraftparität; Dänemark